Synthesis of Bi2S3/C yolk-shell composite based on sulfur impregnation for efficient sodium storage - Kim, Hyeongwoo; Kim, Dowon; Lee, Yongho; Byun, Dongjin; Kim, Hyung-Seok; Choi, Wonchang (ELSEVIER SCIENCE SA, 2020)
Bismuth sulfide (Bi2S3) is considered as an attractive anode material for sodium-ion battery (SIB) systems owing to its high theoretical capacity (625 mAh g(-1)) and laminar structure for storing host ions. However, capacity fading due to the large volume change during long term cycling is a serious problem preventing the practical application of this material to SIBs. Also, its electrical conductivity is still unsatisfactory. To solve those problems, the design of a Bi2S3/C composite with a yolk-shell type structure is proposed. The synthesis method of Bi2S3/C yolk-shell composite includes the fabrication of Bi/C yolk-shell platforms followed by a simple sulfur-impregnation step to obtain Bi2S3/C yolk-shell composites. This sulfur-impregnation step does not result in any degradation of the particle structure and preserves the uniform carbon shell. Furthermore, the Bi2S3/C yolks-shell composite displays enhanced electrochemical performance as an SIB anode material and exhibits high stability during long-term cycling (282.4 mAh g(-1) after 300 cycles at 0.2C) and improved rate capability (413.0 mAh g(-1) at 10C). These improvements are mainly attributed to the conductive electron pathway provided by the carbon shell and the suppression of large volume changes due to the presence of voids in the yolk-shell structure.
Keywords: LITHIUM-ION BATTERIES; FLOWER-LIKE BI2S3; ANODE MATERIAL; FACILE SYNTHESIS; POROUS CARBON; PERFORMANCE; NANOSTRUCTURES; NANOCOMPOSITES; NANOPARTICLES; ELECTRODES